Intraosseous phlebography in bovine osteomyelitis - Das, A K; Singh, A P; Chawla, S K; Singh, Jit (The Indian Journal of Animal Sciences, 2012)
Intraosseous phlebography was performed in 12 calves aged 1 to 1Â½ years at 3, 6, 12 and 18 weeks after experimental induction of osteomyelitis by intramedullary injection of Staphylococcus aureus along with sterilized saw dust in the distal metaphysis of metatarsal bone using 10 ml of sodium iothalmate as contrast medium. Phlebograms at early stages demonstrated marked dilatation and sacculation of the medullary vessel with evidence of stasis and delayed drainage of the contrast material. In 1 animal, flow of the contrast medium stopped just short of well defined radiolucent abscess cavity having sclerotic margin in the proximal metaphysis, while in another calf, flow of the contrast medium took a deviated course and bypassed the abscess cavity. At later stage medullary venous system of the osteomyelitic bone appeared to be completely disrupted without visualization of definite venous channels. The major extraosseous venous channels of the metatarsus were not opacified indicating stasis and delayed clearance of the contrast medium.